2010
DOI: 10.4238/vol9-2gmr791
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of maize single-cross performance by mixed linear models with microsatellite marker information

Abstract: ABSTRACT. We evaluated the potential of the best linear unbiased predictor (BLUP) along with the relationship coefficient for predicting the performance of untested maize single-cross hybrids. Ninety S 0:2 progenies arising from three single-cross hybrids were used. The 90 progenies were genotyped with 25 microsatellite markers, with nine markers linked to quantitative trait loci for grain yield. Based on genetic similarities, 17 partial inbred lines were selected and crossed in a partial diallel design. Simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 22 publications
3
14
2
Order By: Relevance
“…Moreover, in ideal situations, such as those obtained by Bernardo (1994Bernardo ( , 1995, where two distinct heterotic groups are evident, the predictions using the SBD tend to be more accurate and consistent with the observed values. These results were also observed by Balestre et al (2010). However, if distinct groups do not occur and the inbred lines come from different backgrounds the level of information retrieved using the SBD may be minimal and lead to less accurate predictions, as occurred in this study.…”
supporting
confidence: 77%
See 3 more Smart Citations
“…Moreover, in ideal situations, such as those obtained by Bernardo (1994Bernardo ( , 1995, where two distinct heterotic groups are evident, the predictions using the SBD tend to be more accurate and consistent with the observed values. These results were also observed by Balestre et al (2010). However, if distinct groups do not occur and the inbred lines come from different backgrounds the level of information retrieved using the SBD may be minimal and lead to less accurate predictions, as occurred in this study.…”
supporting
confidence: 77%
“…This fact was also observed in several studies where the variance of GCA was higher than the variance of SCA and in these cases, as expected, the predictions were assisted. In this study, although the variance of SCA was greater than the variance of GCA, the difference between the two variances was less pronounced as observed by Balestre et al (2010). Even in this case, the authors observed medium magnitude correlation values between the predicted and observed values.…”
contrasting
confidence: 56%
See 2 more Smart Citations
“…The efficiency of this approach has been demonstrated in several studies of maize (Bernardo, 1994(Bernardo, , 1995(Bernardo, , 1996Schrag et al, 2009;Balestre et al, 2010). In all these studies, a relatively good correlation between phenotypic means and predicted means was observed, demonstrating acceptable accuracy.…”
Section: Introductionmentioning
confidence: 91%